2002
DOI: 10.2298/hel0237109c
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and path analysis in sunflower

Abstract: Fifty-one inbreds and three checks of sunflower were laid in a randomized complete block design following recommended package of practices. Correlation studies revealed that seed yield was positively and significantly associated with seed volume weight, hull percentage, percent autogamy, days to 50 percent flowering and oil yield. Oil content was positively associated with plant height, number of leaves per plant, seed volume weight, hull percentage, head diameter, percent autogamy, days to 50 percent flowerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 2 publications
5
6
0
4
Order By: Relevance
“…Likewise, hundred seed weight and oil content also had high positive direct effects. Oil content had high direct effect on seed yield documented by (Chikkadaviah et al, 2002). Current findings revealed that 100 SW, OC percentage, DFI, DFC and HD can be contemplated as assortment benchmark for direct refinement in seed yield while for indirect improvement, plant height and days to maturity are important traits.…”
Section: Path Coefficient Analysismentioning
confidence: 83%
“…Likewise, hundred seed weight and oil content also had high positive direct effects. Oil content had high direct effect on seed yield documented by (Chikkadaviah et al, 2002). Current findings revealed that 100 SW, OC percentage, DFI, DFC and HD can be contemplated as assortment benchmark for direct refinement in seed yield while for indirect improvement, plant height and days to maturity are important traits.…”
Section: Path Coefficient Analysismentioning
confidence: 83%
“…Avaliação de híbridos de girassol e relação entre parâmetros produtivos e qualitativos A correlação significativa e positiva entre diâmetro de capítulo e massa de mil grãos (r = 0,44**) foi constatada também por Khan (2001), Chikkadevaiah et al (2002), Habib et al (2007) e Machikowa e Saetang (2008). As variáveis número de grãos por capítulo e diâmetro de capítulo apresentaram correlação significativa e positiva (r = 0,71**).…”
Section: Resultsunclassified
“…Machikowa e Saetang (2008) encontraram essa resposta para diâmetro de capítulo, massa de mil grãos e percentagem de grãos normais. Chikkadevaiah et al (2002) encontraram correlação significativa e positiva para massa de mil grãos e diâmetro de capítulo.…”
Section: E Khan (2001)unclassified
See 2 more Smart Citations